UPAYA MENINGKATKAN KEMAMPUAN SISWA MENULIS TEKS PROSEDUR MELALUI MODEL PEMBELAJARAN CHAIN WRITING DI SMP - Rusino, Rusino (Universitas Tanjungpura, 2021)
Abstract This classroom action research was conducted in Class IX A SMP Negeri 5 Kubu with a total of 22 students. The objectives to be achieved in this study are to improve students' ability to compile procedural texts, develop effective, efficient and fun learning strategies and learning models, students can actively involve themselves in communication activities by expressing their ideas, opinions and feelings simply both verbally. or written. The technique used in this research is to make observations / observations and give student performance tests in the form of written tests. Then the next goal of Classroom Action Research is to find out to what extent learning through the Chain writing learning model can improve student learning outcomes in writing procedural texts in class IX A at SMP Negeri 5 Kubu. Classroom action research (CAR) was conducted in 2 cycles, from the results of the actions taken were proven to improve student learning outcomes in English lessons by reaching the KKM standard, namely 70. From 64.31% in cycle I, it could increase to 78.63%. in cycle 2. The results of this action research indicate that the chain writing learning model is effective in improving students' skills in writing procedural texts. Keywords: Chain Writing, Learning Model, Student ability, Procedure Text, Writing